ANALISIS EFEKTIVITAS DAN EFISIENSI PEJABAT PERBENDAHARAAN: STUDI KASUS PADA KANTOR KEMENTERIAN AGAMA - Said, Ali; Subekan, achmat (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2024)
Abstract This study aims to determine the implementation of regulations for treasury officials as well as the effectiveness and efficiency of their performance at the Regency/City Office of Ministry of Religion. Treasury officials are limited to Commitment-Making Officer (PPK), Payment Instruction Signing Officer (PPSPM), and Expenditure Treasurer. The research problem formulation revolves around the implementation, effectiveness and efficiency of treasury officials. The research method used is descriptive quantitative. Research data was obtained through questionnaires, data documentation from the Ministry of Finance, and interviews with key sources or informants. Data validity is maintained by triangulation and obtaining from valid sources. The results of the study show that the implementation of the appointment of treasury officials is in accordance with statutory regulations and takes into account their competencies. PPK has demonstrated good quality performance, in accordance with applicable laws and regulations. PPSPM's performance in general is also good, but still requires improvement in terms of reporting. Meanwhile, the performance of the Expenditure Treasurer is in position 5 (good) on a scale of 6. The treasurer's performance requires improvement, especially in terms of reporting to the State Treasury Services Office and the Financial Audit Agency. With regard to efficiency, it was found that there were inefficiencies in the payment of honorarium for treasury officials. You can still save on honorarium payments without reducing the quality of performance.